Comprehension of the education handout and health literacy of pacemaker users - Jackelline Evellin Moreira dos Santos; Virginia Visconde Brasil; Katarinne Lima Moraes; Jacqueline Andréia Bernardes Leão Cordeiro; Gabriela Ferreira de Oliveira; Carla de Paula Bernardes; Bárbara Ribeiro Miquelin Bueno; Rafaela Peres Boaventura; Fernanda Alves Ferreira Gonçalves; Lizete Malagoni de Almeida Cavalcante Oliveira; Maria Alves Barbosa; Antonio Márcio Teodoro Cordeiro Silva
ABSTRACT Objective: To verify the comprehension of the education handout and the level of Functional Health Literacy of individuals with cardiac pacemaker (PM) and whether there is correlation between the comprehension and Functional Health Literacy (FHL). Method: Cross-sectional study with 63 individuals with PM who answered to comprehension tests of the handout, literacy assessment (SAHLPA-50) and cognition (MMSE). Measurements of dispersion, Pearson correlation and multiple linear regression were calculated. Results: Most women, study time ≤ 9 years, 66.21 (average age) presented no cognitive changes. An adequate literacy level was evidenced in 50.8% individuals with PM and satisfactory comprehension of the handout. No correlation was identified between FHL, handout comprehension, age, years of study and cognition. Conclusion: The handout comprehension assessed by individuals with appropriate FHL indicated that it can be a printed material suitable for use, aiming to improve care process and knowledge of individuals with PM.